Perbedaan Hardiness antara Anak Jalanan yang Mengikuti dan Tidak Mengikuti Program Sahabat Anak - Christina, Arlita; Sandra, Lidia (Noetic Psychology, 2012)
AbstractThe aim of this research was to found the hardiness differences between children on the street who participate in Sahabat Anak program with children whom not participate. Using purposive sampling methods, 60 children around 11-15 years old selected became participant in this research.ÃÂ  Data collected using Disposition Resilience Scale and analyzed using t-test independent sample. The result found F score = 0,256 with significance level 0,165. Based on this result can be conclude tahat there was no significant difference between children on the street whoÃÂ  participate in Sahabat Anak program with children whom not participate. The inmpication of this study showed that children on the street has the ability to deal with problems in their daily life which need to be improved.ÃÂ  Keyword ÃÂ : Children on the street, Hardiness, Sahabat AnakÃÂ